Inhibition of enzymes associated with metabolic and neurological disorder by dried pomegranate sheets as a function of pomegranate cultivar and fruit puree. (22nd October 2020) - Cano‐Lamadrid, Marina; Tkacz, Karolina; Turkiewicz, Igor P; Nowicka, Paulina; Hernández, Francisca; Lech, Krzystof; Carbonell‐Barrachina, Ángel A; Wojdyło, Aneta
Abstract: BACKGROUND: Obesity and type 2 diabetes mellitus are the most extended current chronic diseases and also Alzheimer pathology which is a progressive degenerative neurological disorder. Therefore, finding effective enzyme inhibitors responsible for the development of these diseases are essential. Therefore, the aim of this study was to investigate the impact of fruit purée ( Cydonia oblonga, Ziziphus jujube and Malus domestica ) and pomegranate juice cultivar ('Mollar de Elche' and 'Wonderful') of dried pomegranate sheets (DS) on the inhibition of enzymes associated with metabolic (α‐amylase, α‐glucosidase, and pancreatic lipase activity), and neurological disorder (acetylcholinesterase and butyrylcholinesterase activity). Quality properties (colour coordinates, texture properties and sensory characteristics) of DS were also studied. In addition, it was researched the effect of storage conditions (4 months at 4 and 20 °C) on phenolic content. RESULTS: DS from jujube had the highest antioxidant capacity and were characterized by the highest storage stability with respect to phenolic compounds. The α‐amylase and α‐glucosidase half maximal inhibitory concentration (IC50, in mg mL −1 ) inhibition of DS ranged from 107 to 216 and from 55.2 to values indicating no effect, respectively. The inhibition toward pancreatic lipase (IC50  < 5 mg mL −1 ), acetylcholinesterase (ranged 9.15–22.2%) and butyrylcholinesterase (ranged 20.6–48.6%) was increased with the presence of total flavonoids and hydroxycinnamic acids content (identifying mainly in DS from quinces). It is noteworthy that none of the samples presented off‐flavour notes, supporting the high quality of the products. CONCLUSION: DS can be an innovative supplement to a diet as a snack used in the prevention of neurological changes and disorders of carbohydrate and lipid metabolism. © 2020 Society of Chemical Industry